PENGARUH KUALITAS LAYANAN PUBLIK DI KANTOR DESA BAJERA TERHADAP KEPUASAN MASYARAKAT - Ni Putu Widiastuti; I Wayan Astawa; Ummi Latifah (Universitas Triatma Mulya, 2022)
This study aims to determine the effect of independent variables such as physical ability, reliability, responsiveness, assurance and empathy on the number of community satisfaction visits at the Bajera Village Office. This research is a descriptive analysis research using a quantitative approach. Data collection using a questionnaire. The sample in this study amounted to 100 people and the validity test used Alpha Cronbach. Data analysis using multiple linear regression. The variable of physical ability has a positive and insignificant effect on community satisfaction, it is obtained a sig.t value of 0.256 with a sig value of 0.799> α (0.05) meaning that H0 is accepted. The guarantee variable has a positive and insignificant effect, where the sig.t value of 0.651 with a sig value of 0.517> α (0.05) means that H0 is accepted. The simultaneous test itself has a significant positive effect simultaneously (simultaneously) of physical ability, reliability, responsiveness, assurance and empathy, the results of the F-count value of 23.800 and sig 0.000 on community satisfaction.